Pengaruh Sistem Operasional Dan Komersil (Siopskom) Terhadap Kinerja Personil Airport Operation Landside, Terminal, and Service Improvement Bandar Udara Internasional Zainuddin Abdul Madjid Lombok - Nursyaf, Putri Calista; Ubaedillah; Rini Sadiatmi (FTK UNSURYA, 2026)
This study was conducted at Zainuddin Abdul Madjid International Airport in Lombok to explore the impact of the Operations and Commercial Information System (SIOPSKOM) on the performance of staff within the Airport Operation Landside, Terminal, and Service Improvement (AOLTSI) unit. Through a quantitative approach supported by surveys and field observations, the study reveals a positive correlation between the implementation of SIOPSKOM and improvements in employee performance. Respondents indicated that the system facilitates timely access to information, enhances job efficiency, and supports daily operational tasks more effectively. The findings suggest that SIOPSKOM plays a crucial role in streamlining workflows and promoting a more data-driven work environment. Most staff members acknowledged the system’s relevance in accelerating decision-making and improving service delivery to airport users. These results highlight the importance of maintaining and upgrading digital infrastructure in airport operations. To maximize its potential, the study recommends continuous training for personnel and regular system evaluations to ensure responsiveness to operational needs. The integration of such systems must also be aligned with organizational goals to support a culture of performance accountability and service excellence in the broader context of airport management.